2012
DOI: 10.1007/s10006-012-0329-6
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral, isolated amaurosis after inferior alveolar nerve block: report of two rare cases

Abstract: Though permanent amaurosis has been reported, it is usually transient in nature. Various causes have been proposed like intravascular injection, sympathetic impulse generation, and embolism. The etiology in the present case was believed to be intravascular injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Diplopia was reported as an adverse effect in 14 studies, but disappeared after 15 min to 24 h [ 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ]. Complete or partial loss of vision [ 24 26 29 37 38 39 ], strabismus [ 27 ], blurred vision [ 31 40 ], and uniocular blindness [ 34 41 ] were also reported, but were all temporary. Rishiraj et al [ 42 ] described a case of permanent vision loss in one eye after administration through a combination of IANB and infiltration anesthesia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diplopia was reported as an adverse effect in 14 studies, but disappeared after 15 min to 24 h [ 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ]. Complete or partial loss of vision [ 24 26 29 37 38 39 ], strabismus [ 27 ], blurred vision [ 31 40 ], and uniocular blindness [ 34 41 ] were also reported, but were all temporary. Rishiraj et al [ 42 ] described a case of permanent vision loss in one eye after administration through a combination of IANB and infiltration anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…The reported adverse effects covered in this review were divided into 12 categories because of their large scale and variety. Ocular adverse effects were cited most frequently and reported in 23 articles [ 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 ]. Ocular alterations consisted of visual disturbances, paralysis of the eye muscles, and numbness of the eyelids or eyebrows.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,17,18,[27][28][29][30][31][32] The duration of visual loss in most previous cases was no longer than a few hours. This implies that the symptoms subside as the local anesthesia effect disappears.…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…Various causes for ocular complications due to intraoral local anesthesia are as follows: 6,7 • Diffusion • Inadvertent needle penetration into the orbit • Venous injection • Retrograde arterial injection • Sympathetic impulse generation • Embolism.…”
Section: Common Ocular Complicationsmentioning
confidence: 99%
“…The etiology in the present case was believed to be intravascular injection. 7 Steenen et al (2012) reviewed the literature from the years 1936 to 2011 and showed 131 cases with this type of complication and also presented a case report of a patient with right lateral rectus muscle palsy and blurred vision after bimaxillary anesthesia. Signs, symptoms and pathophysiologic hypotheses of these complications were presented.…”
Section: Literature Reviewmentioning
confidence: 99%